2020
DOI: 10.1021/acs.analchem.0c03240
|View full text |Cite
|
Sign up to set email alerts
|

Xurography-Enabled Thermally Transferred Carbon Nanomaterial-Based Electrochemical Sensors on Polyethylene Terephthalate–Ethylene Vinyl Acetate Films

Abstract: A novel benchtop approach to fabricate xurography-enabled thermally transferred (XTT) carbon nanomaterial-based electrochemical sensors is proposed. Filtered nanomaterial (NM) films were transferred from Teflon filters to polyethylene terephthalate–ethylene vinyl acetate (PET-EVA) substrates by a temperature-driven approach. Customized PET-EVA components were xurographically patterned by a cutting plotter. The smart design of PET-EVA films enabled us to selectively transfer the nanomaterial to the exposed EVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Films based exclusively on nanomaterials and their integration into flexible plastic and paper substrates to fabricate cutting-edge sensors and devices represent a hot research topic . In this regard, graphene and graphene-like materials, carbon black, , and carbon nanotubes have been extensively studied, while fully biochar-based films for electroanalytical purposes are not yet exploited. Probably, this lack can be attributed to heterogeneous structures of biochar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Films based exclusively on nanomaterials and their integration into flexible plastic and paper substrates to fabricate cutting-edge sensors and devices represent a hot research topic . In this regard, graphene and graphene-like materials, carbon black, , and carbon nanotubes have been extensively studied, while fully biochar-based films for electroanalytical purposes are not yet exploited. Probably, this lack can be attributed to heterogeneous structures of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, miniaturized electrochemical platforms move toward low-impact materials (cellulose, polylactic acid, recyclable flexible plastics, etc.) and affordable lab-attainable manufacturing technologies. ,, In this regard, biochar may represent potentially the “gold material”, considering the sustainability, versatility, and effectiveness. Biochar integration onto innovative “supports” represents a new compelling research field in environmental remediation and also in material science, wherein particular biochar nanofibers are used to construct electrospun, electrospun-based polymers, and modified textiles .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different commercially available CBs, an interesting study by Mazzaracchio et al [ 5 ] demonstrated the superior electron transfer ability of the N220 type. For this reason, this type of CB has been largely employed for electrochemical sensor/device implementation using different approaches: electrode modification via drop casting [ 7 , 8 , 9 , 10 , 11 ], fabrication of transducers via press/thermal transfer [ 12 , 13 , 14 , 15 ], or CB inclusion in conductive inks/pastes [ 16 , 17 ]. The classical strategy to prepare/disperse CB for electroanalytical purposes relies on its dispersion in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…So far, laser toner has found applications, i.a., as a hydrophobic barrier for valves and droplet handling [ 25 , 26 ] and a material for formation of microstructures, as well as a thermo-responsive adhesive that enables lamination [ 27 , 28 ]. A number of microfluidic analytical systems using PET-toner interfaces have been developed for applications such as capillary electrophoresis [ 29 ], separation of nucleic acids [ 30 , 31 ], and chemical and biochemical assays (using colorimetric or enzymatic reactions) for the determination of relevant analytes [ 32 , 33 , 34 , 35 ]. Until now, laser toner has not been considered in a construction of immunoassays as a readily applied, hydrophobic substrate for the direct, passive immobilization of antibodies.…”
Section: Introductionmentioning
confidence: 99%